Latent heat storage particles, heat exchange material, and method for producing latent heat storage particles
The covering particles are attached to the surface of the core material particles by high-speed air impact method, which solves the problems of complex and unstable PCM packaging in the prior art, and realizes the efficient and stable manufacturing of latent heat storage particles.
Patent Information
- Application Number
- JP2023546970
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-07
- Filing Date
- 2022-09-07
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2042-09-07
AI Technical Summary
The prior art requires chemical coating treatment and high temperature baking when manufacturing -latent heat storage bodies, and the process is complex and there are difficulties in microencapsulation of metal-aluminum alloy PCM.
The high-speed air impact method is used to collide and combine the core material particles with the covering particles to form a covering layer, thereby achieving the micro-encapsulation of PCM and enhancing the density and stability of the covering layer through heat treatment.
It realizes stable packaging of PCM, avoids leakage problems during PCM flow, and has a relatively simple process, suitable for PCM core materials with a variety of thermal storage temperatures.
Smart Images

Figure 0007669068000006 
Figure 0007669068000007 
Figure 0007669068000008
Abstract
Description
[Technical field]
[0001] The present disclosure relates to latent heat storage particles, heat exchange materials, and methods for making latent heat storage particles. [Background technology]
[0002] There are two known methods of storing heat: sensible heat storage, which utilizes temperature changes, and latent heat storage, which utilizes the phase change of a substance. Of these, sensible heat storage technology can store heat at high temperatures, but has the problem of low heat storage density because it only uses sensible heat due to temperature changes in the substance. On the other hand, latent heat storage technology uses the latent heat of solid-liquid phase change of phase change materials (PCMs), so it can store heat at a higher density than sensible heat storage technology. In addition, it is attracting attention in the fields of solar heat utilization and waste heat utilization because it is possible to collect, transport, and supply waste heat derived from reaction heat at a constant phase change temperature. PCMs melt and become liquid during heat storage, so they need to be encapsulated to prevent leakage of the liquid PCM. Various methods have been proposed to encapsulate PCMs.
[0003] For example, Patent Document 1 proposes a latent heat storage capsule in which the surface of a latent heat storage material is coated with a metal coating of one, two or three layers, and a latent heat storage capsule in which a metal coating is coated on a latent heat storage material by electrolytic plating. Patent Document 2 also proposes a heat storage microcapsule having a core coated with a shell, the core containing at least one water-soluble latent heat storage material selected from salt hydrates and sugar alcohols, and a polymer obtained from a water-soluble monomer mixture of a water-soluble monofunctional monomer and a water-soluble polyfunctional monomer, and the shell being formed from a hydrophobic resin, and a method for producing the same. This technology is a microencapsulation technology for PCM, which has a relatively low melting point.
[0004] Patent Document 3 proposes a heat storage body having an internal heat storage body made of a material having heat storage properties and an outer shell made of ceramics having a relative density of 75% or more, which contains the internal heat storage body. The internal heat storage body is made of a metal containing at least one selected from the group consisting of Al, Mg, Sn, Zn, and Cu, or made of a carbonate compound, hydroxide, chloride, or a composite thereof containing at least one selected from the group consisting of K, Li, Na, Ca, and Mg, and the material of the outer shell (capsule) is made of at least one selected from the group consisting of alumina, silicon nitride, and silicon carbide, or a composite containing at least one selected from the group. The technology of Patent Document 3 is a technology in which a PCM having a melting point in a high temperature range is encapsulated.
[0005] The latent heat storage capsule of Patent Document 1 has a metal coating with low heat resistance, so it is difficult to maintain the metal coating at high temperatures, and it is considered difficult to use it at high temperatures. Also, the heat storage microcapsule described in Patent Document 2 is considered difficult to use in harsh environments where high temperatures and corrosion are likely to occur. Furthermore, the heat storage body described in Patent Document 3 has an outer shell made of ceramics, and is considered to have excellent heat resistance and corrosion resistance, but is considered difficult to mold and process.
[0006] In view of the above problems, the present inventors have proposed in Patent Document 4 a latent heat storage microcapsule, a method for producing a latent heat storage, a heat exchange material, and a catalytically functional latent heat storage material, in which the surface of a core particle made of a metal or alloy latent heat storage material is covered with an oxide film of the constituent elements of the core particle. Patent Document 5 also proposes a latent heat storage material having a core part and a coating layer, and a BET specific surface area of 10 m 2 / g or more. These techniques eliminate the need for a process for separately preparing the core particles and the oxide film corresponding to the shell that contains the core particles, and then accommodating the core particles inside the shell. In addition, since the core particles do not expand when the phase is transformed from solid to liquid, the components of the molten latent heat storage material remain inside the space covered by the oxide film, and the oxide film is not damaged. In addition, the oxide film can be made chemically stable. Furthermore, according to Patent Document 5, the material of the core part can be easily captured, and the occurrence of leakage of the core part can be reduced. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-23172 [Patent Document 2] JP 2012-140600 A [Patent Document 3] JP 2012-111825 A [Patent Document 4] JP 2019-173017 A [Patent Document 5] JP 2019-203128 A Summary of the Invention [Problem to be solved by the invention]
[0008] The manufacturing method of the latent heat storage material shown in Patent Document 4 and Patent Document 5 requires chemical coating treatment and subsequent firing at high temperature, and there is a demand for a simpler manufacturing method of the latent heat storage material. In addition, when a metal / alloy PCM not containing Al is used as a core particle, it is difficult to perform microencapsulation by the conventional manufacturing method. The present disclosure has been made in consideration of the above circumstances, and its purpose is to provide a manufacturing method of latent heat storage particles that can easily manufacture latent heat storage particles in which PCM leakage is suppressed and the structure is stable even after heat storage cycles. Furthermore, it is an object of the present disclosure to provide latent heat storage particles in which PCM leakage is suppressed and the structure is stable even after heat storage cycles, and a heat exchange material formed from the latent heat storage particles. [Means for solving the problem]
[0009] Aspect 1 of the present invention is The present invention has a core particle and a coating portion that coats at least a portion of the surface of the core particle, The component of the core particle is an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy or compound containing these as a main component, and has a melting point of 100° C. or higher; a component of the coating portion is one or more selected from the group consisting of an element, an alloy and an inorganic compound containing the element, and a mixture thereof, which does not undergo a chemical reaction with the core particle in a temperature range of an operating temperature and is different from the component of the core particle; At least a part of the coating portion is in the form of latent heat storage particles.
[0010] Aspect 2 of the present invention is In the latent heat storage particle according to aspect 1, the average particle size of the core particles is 10 μm or more and 200 μm or less.
[0011] Aspect 3 of the present invention is At least a part of the particle shape of the coating portion is the latent heat storage particle according to aspect 1 or 2, and the average particle diameter is 0.1 μm or more and 2 μm or less.
[0012] A fourth aspect of the present invention is The latent heat storage particle according to any one of aspects 1 to 3, wherein the component of the core particle is one or more selected from the group consisting of Al, an Al-Si alloy, an Al-Cu-Si alloy, Sn, an Sn alloy, and a Zn-Al alloy.
[0013] A fifth aspect of the present invention is In the latent heat storage particle according to any one of Aspects 1 to 4, the inorganic compound in the component of the coating portion is one or more selected from the group consisting of ceramics, glass, and an α-alumina precursor which becomes α-Al2O3 upon firing.
[0014] A sixth aspect of the present invention is In the latent heat storage particle according to any one of Aspects 1 to 5, a component of the coating portion is one or more selected from the group consisting of Al, α-Al2O3, AlOOH, Al(OH)3, and glass.
[0015] A seventh aspect of the present invention is The latent heat storage particle according to any one of aspects 1 to 6, wherein the coating portion contains one or more selected from the group consisting of an element constituting the core particle, an alloy and an inorganic compound containing the element, and a mixture thereof.
[0016] Aspect 8 of the present invention is A heat exchange material formed of the latent heat storage particles according to any one of the first to seventh aspects.
[0017] A ninth aspect of the present invention is A core raw material particle having a melting point of 100° C. or higher, the component of which is an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy or compound containing these as a main component; A component is one or more selected from the group consisting of an element, an alloy and an inorganic compound containing the element, and a mixture thereof, which is different from the component (particularly the main component) of the core particle and does not undergo a chemical reaction with the core particle in the temperature range of operation temperature; and The core material particles and the child particles are collided with each other by an impact method in a high-speed air stream, thereby performing hybridization in which the child particles are fixed to the surfaces of the core material particles. The method for producing latent heat storage particles includes the steps of:
[0018] A tenth aspect of the present invention is The average particle size of the core raw material particles is 10 μm or more and 200 μm or less, The average particle size of the child particles is 0.1 μm or more and 2 μm or less, In the method for producing latent heat storage particles according to aspect 9, the ratio of (average particle size of child particles / average particle size of core raw material particles) is 0.001 or more and 0.2 or less.
[0019] An eleventh aspect of the present invention is In the method for producing latent heat storage particles according to aspect 9 or 10, the hybridization is carried out at a peripheral speed of 40 m / s or more and 100 m / s or less.
[0020] A twelfth aspect of the present invention is In the method for producing latent heat storage particles according to any one of Aspects 9 to 11, after the hybridization, a heat treatment is carried out at a temperature equal to or higher than the melting point of the component of the core raw material particle. Effect of the Invention
[0021] According to the present invention, it is possible to provide latent heat storage particles in which leakage of PCM is suppressed and the structure is stable even after a heat storage cycle, and a heat exchange material formed from the latent heat storage particles.Furthermore, it is possible to provide a method for easily producing the latent heat storage particles. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view of a high-speed airflow impact device. [Diagram 2] FIG. 2 is a SEM micrograph of a sample after hybridization in an embodiment. [Diagram 3]FIG. 3 is a SEM micrograph of a sample after repeated testing in the example. [Figure 4] FIG. 4 shows the results of XRD measurement in the examples. [Diagram 5] FIG. 5 shows the results of differential scanning calorimetry in the examples. [Figure 6] FIG. 6 is a SEM micrograph of a sample after the heat durability test in the example. [Figure 7] FIG. 7 shows the results of XRD measurement in the examples. [Figure 8] FIG. 8 is a SEM micrograph of a sample in the example. [Figure 9] FIG. 9 is a STEM-EDS photograph of a sample in the example. [Figure 10] FIG. 10 is a photograph of particles constituting the coating portion of a sample in the example. [Figure 11] FIG. 11 is a photograph of particles constituting the coating portion of a sample in the example. [Figure 12] FIG. 12 is a photograph of particles constituting the coating portion of a sample in the example. [Figure 13] FIG. 13 shows the results of differential scanning calorimetry of the samples in the examples. [Figure 14] FIG. 14 shows the results of differential scanning calorimetry of the samples in the examples. [Figure 15] FIG. 15 is a SEM micrograph of the raw material particles used in the examples. [Figure 16] FIG. 16 is a SEM micrograph of a sample after hybridization in an example. [Figure 17] FIG. 17 shows SEM micrographs of a sample before and after a cyclic test in an embodiment. [Figure 18] FIG. 18 is a SEM micrograph of a sample after hybridization in an example. [Figure 19] FIG. 19 is a SEM micrograph of a sample after heat treatment in the example. [Figure 20] FIG. 20 is a SEM micrograph of a sample after heat treatment in the example. [Figure 21] FIG. 21 is a SEM micrograph of a sample after heat treatment in the example. [Figure 22] FIG. 22 is a SEM micrograph of a sample after heat treatment in the example. [Diagram 23] FIG. 23 shows the results of XRD measurement of the heat-treated sample in the example. [Figure 24] FIG. 24 shows the results of XRD measurement of the heat-treated sample in the example. [Diagram 25] FIG. 25 shows the results of differential scanning calorimetry of the sample after heat treatment in the example. [Figure 26] FIG. 26 shows the results of differential scanning calorimetry of the sample after heat treatment in the example. [Figure 27] FIG. 27 shows SEM micrographs of a sample before and after a cyclic test in an embodiment. [Figure 28] FIG. 28 is a SEM micrograph of a sample in the example. [Figure 29] FIG. 29 is a SEM micrograph of a sample in the example. [Diagram 30] FIG. 30 is a SEM micrograph of a sample in the example. [Diagram 31] FIG. 31 shows the results of differential scanning calorimetry of the samples in the examples. [Diagram 32] FIG. 32 shows the results of differential scanning calorimetry of the samples in the examples. [Diagram 33] FIG. 33 shows the results of differential scanning calorimetry of the samples in the examples. [Diagram 34] FIG. 34 shows the results of differential scanning calorimetry of the samples in the examples. [Diagram 35] FIG. 35 shows the results of differential scanning calorimetry of the samples in the examples. [Diagram 36] FIG. 36 shows SEM micrographs of a sample before and after a cyclic test in an embodiment. [Figure 37] FIG. 37 shows the results of differential scanning calorimetry of the samples in the examples. [Figure 38]FIG. 38 is a SEM micrograph of a sample in the example. [Figure 39] FIG. 39 shows the results of differential scanning calorimetry of the samples in the examples. [Diagram 40] FIG. 40 shows the results of differential scanning calorimetry of the samples in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] As a result of intensive research, the inventors have found that by colliding core raw material particles and child particles of a predetermined composition by a high-speed airflow impact method, it is possible to easily obtain latent heat storage particles that are structurally stable even after a heat storage cycle, while suppressing leakage of PCM. The latent heat storage particles according to this embodiment, the heat exchange material formed from the latent heat storage particles, and the method for producing the latent heat storage particles will be described below.
[0024] [Latent heat storage particles] [Core particle] The core particle is composed of an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy or compound mainly composed of these, and has a melting point of 100°C or higher. The "main component" means that the ratio of the entire core particle is 50 mass% or more. As described above, the component constituting the core particle needs to not melt when forming the coating portion during the production of the latent heat storage particle, and needs to have a melting point of 100°C or higher. The core particle is a phase change material (PCM) that can utilize the latent heat of solid-liquid phase change, and the heat of fusion can be preferably, for example, 150 J / g or more, and a high amount of latent heat can be secured.
[0025] As described above, components constituting the core particle include Sn (melting point 232°C), In (melting point 157°C), Bi (melting point 272°C), Pb (melting point 328°C), and Cd (melting point 321°C), which have a lower melting point than Al. In addition, Cu (melting point 1085°C), which has a higher melting point than Al, can be used. By using these components as the core particles of latent heat storage particles, latent heat storage particles with a different heat storage temperature from latent heat storage particles whose core particles are Al or Al alloys that have been used conventionally can be realized. In consideration of the environment, metals selected from the group consisting of Al, Mg, Sn, Zn, Bi, In, and Cu, or alloys mainly composed of these metals are preferred.
[0026] More preferred components of the core particles include Sn and Sn alloys mainly composed of Sn. By including Sn in the core particles, a PCM having a lower heat storage temperature (melting point) can be easily realized than latent heat storage particles having Al as the core particles. Examples of the Sn alloy include Sn-Zn alloys. The Zn content of the Sn-Zn alloy is more than 0 mass% and less than 50 mass%, and can be 20 mass% or less, and further 10 mass% or less. More preferably, the core particles are formed of Sn.
[0027] Another preferred component of the core particles is an alloy of Al and Si (Al-Si alloy). In this case, the Si content is not particularly limited as long as it is more than 0 mass% and less than 100 mass%. For example, the Si content can be in the range of 10 mass% or more and 90 mass% or less. Within this range, the Si content may be 10 mass% or more and 25 mass% or less.
[0028] Yet another preferred component of the core particle is an Al alloy containing Cu and Si (Al-Cu-Si alloy). The contents of Cu and Si contained in the Al-Cu-Si alloy are not particularly limited, and it is sufficient that each of Cu and Si is more than 0 mass% and the total of Cu and Si is 90 mass% or less.
[0029] Another preferred component of the core particles is an alloy of Zn and Al (Zn-Al alloy). In this case, the Al content is not particularly limited as long as it is more than 0 mass% and less than 100 mass%. The Al content may be 50 mass% or less.
[0030] The core particle may be made of metallic Al with an Al concentration of 100% without containing any alloying components.
[0031] The average particle diameter of the core particles is preferably 10 μm or more and 200 μm or less. According to this embodiment, the core particles (PCM) are the above components, and latent heat storage particles of the micro order can be realized. The average particle diameter may be, for example, 100 μm or less, and even 50 μm or less. In this specification, the "average particle diameter" of the core particles and the core raw material particles and child particles described later is a value measured by a laser diffraction type particle size distribution meter (e.g., HORIBA LA-920). More specifically, the volume distribution of the particle group is measured by a laser diffraction type particle size distribution meter, and the value of the cumulative 50 volume % diameter (D50) is regarded as the average particle diameter. The average particle diameter of the core particles constituting the latent heat storage particles may be approximately the same as the average particle diameter of the core raw material particles used in the production of the latent heat storage particles, or may be smaller than the average particle diameter of the core raw material particles. According to this embodiment, the latent heat storage particles need only have a core-shell structure, and even if, during the manufacturing stage or use of the latent heat storage particles, a portion of the surface of the core raw particle reacts with, for example, a child particle, the outside air, etc., and, for example, a portion of the surface of the core raw particle made of a metal is changed to an oxide, and some of the metal constituting the core raw particle is consumed, the latent heat storage particles can still function as long as they maintain the core-shell structure.
[0032] [Covering part] The components of the coating portion are composed of one or more selected from the group consisting of elements, alloys and inorganic compounds containing the elements, and mixtures thereof, which are different from the components of the core particles and do not undergo a chemical reaction with the core particles in the temperature range of the operating temperature. The operating temperature can be in the range of 100°C or higher and 1500°C or lower. The elements can be elements selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd. The inorganic compounds can also include mixtures of two or more different inorganic compounds. The inorganic compounds are preferably one or more selected from the group consisting of ceramics, glass, and α-alumina precursors that become α-Al2O3 by firing. The ceramics can be aluminas such as α-Al2O3 and θ-Al2O3, SiO2 (silica), etc. The α-alumina precursor is a compound that becomes α-Al2O3 by firing at a temperature of, for example, 880° C. or higher, and examples of the α-alumina precursor include Al-containing compounds, Al-containing oxides and / or Al-containing hydroxides, AlOOH, and / or Al(OH)3. The component of the coating portion is more preferably one or more selected from the group consisting of Al, α-Al2O3, AlOOH, Al(OH)3, and glass.
[0033] When the core particle is a metal or alloy and the coating is ceramic, the metal contained in the core particle and the metal element contained in the ceramic constituting the coating may be the same or different. For example, when the core particle is an Al alloy and the coating is an Al oxide, the component of the coating is an oxide, which is different from the alloy that is the component of the core particle, but the metal Al contained in the core particle and the metal element (Al) contained in the oxide as the ceramic constituting the coating are the same.
[0034] The coating portion of the latent heat storage particles according to this embodiment may have a thickness in the range of 200 nm to 5 μm. The coating portion may be, for example, a coating layer having a thickness of 1 to 2 μm.
[0035] The coating part of the latent heat storage particle according to this embodiment may cover at least a part of the surface of the core particle. The coverage of the coating part on the surface of the core particle is preferably 50% by area or more. The coverage is more preferably 70% by area or more, even more preferably 80% by area or more, even more preferably 90% by area or more, and most preferably 100% by area. In the latent heat storage particle according to this embodiment, the core particle may be covered with the components of the coating part without gaps to form a dense shell, or, as long as the range of the preferred coverage is satisfied, it is acceptable that the core particle is not covered with the components of the coating part without gaps and exposed parts are scattered, and that gaps at the nano level, for example, are present due to the accumulation of the child particles. Even if the exposed parts and gaps of the core particle exist, it is considered that deterioration of the core particle due to use can be prevented. As shown in the examples described later, for example, in the case of a core particle made of metal, an oxide is formed at the exposed parts of the core particle exposed to the outside air, and the progress of deterioration due to consumption of the metal of the core particle is prevented.
[0036] The latent heat storage particle according to this embodiment is different from conventional latent heat storage particles in that at least a part of the coating portion has a particulate shape. The particulate shape of at least a part of the coating portion may be derived from the child particles used when manufacturing the latent heat storage particles. The particulate shape of at least a part of the coating portion is confirmed regardless of the presence or absence of the heat treatment described below, and even if the heat treatment described below is performed, it can be confirmed at least in the outermost surface layer region of the coating portion. The particulate shape of at least a part of the coating portion may be an aggregate of particles, and may be an aggregate of the child particles used when manufacturing the heat storage particles. Therefore, the phrase "at least a part of the coating portion has a particulate shape" of the latent heat storage particle means that at least 10 particles (some of which may be joined to other particles) are confirmed when observed with a scanning electron microscope at a magnification of 10,000 times.
[0037] At least a part of the particle shape of the coating portion may have an average particle diameter of 0.1 μm or more and 2 μm or less. This average particle diameter refers to the average equivalent circle diameter of at least 10 particles observed with the electron microscope. The region of the coating portion other than the region of the at least a part of the particle shape may be, for example, a porous or dense solid layer formed by melting and agglomerating child particles.
[0038] The coating portion may contain one or more (core particle-derived components) selected from the group consisting of the elements constituting the core particle, alloys and inorganic compounds containing the elements, and mixtures thereof. As described above, the elements constituting the core particle include elements selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd. The inorganic compounds include ceramics containing the elements and glasses containing the elements. The core particle-derived components contained in the coating portion may contain the elements constituting the core particle, and the form of the core particle-derived components may be the same as or different from that of the core particle components. An example of a case where the forms of the two are different is when the core particle components are metals and the core particle-derived components are oxides of the metals.
[0039] That the core particle-derived component is "contained" in the coating portion means that at least a portion of the core particle-derived component is in contact with the component constituting the coating portion, and examples of this include that the entire core particle-derived component is covered with the component constituting the coating portion, that a portion of the core particle-derived component is covered with the component constituting the coating portion, and the other portion of the core particle-derived component is exposed to the outside air (for example, that it is in contact with a portion of the surface of the coating portion).
[0040] (Heat exchange material made of latent heat storage particles) The present disclosure includes a heat exchange material formed of the latent heat storage particles according to the present embodiment. As the heat exchange material, the latent heat storage particles according to the present embodiment may constitute at least a part of the heat exchange material, and may be, for example, dispersed and contained in a thermal base material, or dispersed and supported in a porous material. Examples of the heat exchange material include, but are not limited to, heat storage bricks, heat storage ceramic balls, and porous ceramic filters.
[0041] [Method of manufacturing latent heat storage particles] The method for producing latent heat storage particles according to the present embodiment includes preparing core raw material particles of a predetermined component and child particles of a predetermined component, and performing hybridization by colliding the core raw material particles and the child particles by impacting in a high-speed air stream to fix the child particles to the surface of the core raw material particles. According to this production method, unlike conventional methods for producing latent heat storage particles, microencapsulation can be realized even when the core raw material particles are made of metal / alloy PCMs that do not contain Al. In addition, latent heat storage particles having PCMs with various heat storage temperatures as core particles can be produced. Furthermore, the surfaces of the core raw material particles can be easily coated with materials other than alumina, and latent heat storage particles in which the coating portion is formed of a material other than alumina can be easily produced. Each step will be described below.
[0042] [Preparation of raw material particles] As the raw material particles, core raw material particles and child particles for forming the coating portion are prepared. The core raw material particles may be prepared to correspond to the core particles of the desired latent heat storage particles, for example, with an average particle diameter of 10 μm or more and 200 μm or less. Even if the core raw material particles contain fine particles with a particle diameter of less than 10 μm, relatively large particles, for example, about 30 μm, may be obtained during hybridization, for example, by the fine particles colliding with each other. The average particle diameter may be, for example, 100 μm or less, or even 50 μm or less. The average particle diameter of the child particles is preferably 0.1 μm or more and 2 μm or less, and the ratio of (average particle diameter of child particles / average particle diameter of core raw material particles) is preferably 0.001 or more and 0.2 or less. The average particle diameter of the child particles may be further 1.0 μm or less, or even 0.4 μm or less. The components of the core raw material particles are the same as the components of the core particles of the latent heat storage particles, and are as described above for the components of the core particles of the latent heat storage particles. The components of the child particles are the same as the components (particularly the main components) of the coating portion of the latent heat storage particles, and are as described above for the components of the coating portion of the latent heat storage particles. When heat treatment is performed at a temperature equal to or higher than the melting point of the components of the core raw material particles after hybridization, or when melting and solidifying are repeatedly performed as in the repeated tests performed in the examples, the components of the coating portion of the latent heat storage particles may be oxides of the components of the child particles, and the components of the coating portion of the latent heat storage particles may include oxides of the core raw material particles, as described above.
[0043] The blending ratio of the core material particles and the child particles to be fed into the device may be such that the ratio of the child particles to the total of the core material particles and the child particles is in the range of 10% by volume or more and 50% by volume or less.
[0044] The third component other than the core material particles and the child particles may include additives such as binders and antioxidants. The allowable amount of the third component may be 40% by volume or less when the amount of the child particles is 100% by volume.
[0045] [Hybridization of core particles and child particles by high-velocity airflow impact method] In this embodiment, core raw material particles and child particles for forming a coating portion are used, and the child particles are mechanically struck against the surface of the core raw material particles by a high-speed airflow impact method, which is a dry mechanical method, to obtain latent heat storage particles in which the child particles are adhered to the surface of the core raw material particles. The "adhesion" includes physical adhesion due to a change in shape of the child particles, as well as adhesion due to a chemical reaction between the core raw material particles and the child particles. The degree of adhesion is not limited, and it is sufficient that at least a part of the surface of the core particles is covered. The higher the coverage rate of the coating portion on the surface of the core particle, the more preferable it is, and as described above, it is preferably 50 area% or more, more preferably 70 area% or more, even more preferably 80 area% or more, even more preferably 90 area% or more, and most preferably 100 area%.
[0046] Hereinafter, the high-velocity air current impact method used in the manufacturing method according to this embodiment will be described with reference to FIG. 1 which shows a schematic diagram of a high-velocity air current impact device, but the present disclosure is not limited to this embodiment.
[0047] 1 is a schematic cross-sectional view of a high-velocity airflow impact device 100 for carrying out hybridization by the high-velocity airflow impact method. The high-velocity airflow impact device 100 is equipped with a raw material particle inlet 1, a rotor 2 rotating at high speed, blades 3, a stator 4, a circulation circuit 5, a discharge valve 6, and a discharge port 7.
[0048] In the high-speed airflow impact method, first, the core raw material particles 8, which are powder, and the child particles 9, which are fine powder, are fed into the impact chamber from the sample inlet 1, and the core raw material particles 8 and the child particles 9 in the impact chamber are scattered while rotating at high speed in the impact chamber due to the rotation of the rotor 2, during which the child particles 9 collide with the surface of the core raw material particles 8. Some of the raw material particles enter the tube from one connection port of the circulation circuit 5 connected to this collision chamber and circulate, and are then introduced back into the collision chamber from the other connection port. This circulation circuit 5 allows the core raw material particles 8 and the child particles 9 to be repeatedly subjected to a collision process. In this way, by continuing the collision due to rotation for a certain period of time, the child particles 9 are fixed to the surface of the core raw material particles 8, and further, the latent heat storage particles 10 formed by the deformation of the child particles 9 are obtained. During the collision between the core raw material particles 8 and the child particles 9, the inlet path to the outlet 7 is closed by the discharge valve 6, but after a certain time, the obtained latent heat storage particles 10 are discharged from the outlet 7 to the outside of the device through the inlet path to the outlet 7 that is opened by moving the discharge valve 6. Although not shown, a cooling water passage may be provided to prevent the temperature inside the collision chamber from becoming too high, and the collision process may be performed while cooling by flowing cooling water. According to the high-speed airflow impact method, latent heat storage particles having a combination of materials of core raw material particles and child particles that could not be obtained in the past can be produced. In addition, the latent heat storage particles can be obtained in a dry manner, without the need to use an organic solvent, and can be obtained in a short time, so that latent heat storage particles can be produced efficiently and stably.
[0049] The peripheral speed of the rotor 2 in the above-mentioned device can be, for example, in the range of 40 m / s or more and 100 m / s or less. The processing time can be, for example, in the range of 1 to 120 minutes, depending on the processing amount. The processing temperature can be, for example, in the range of room temperature to 70°C, and further in the range of room temperature to 50°C. The pressure and atmosphere of the collision chamber are not particularly limited. The atmosphere of the collision chamber can be, for example, an inert gas atmosphere such as an Ar atmosphere.
[0050] The latent heat storage particles obtained by the hybridization may have a porous coating formed by aggregation of child particles, and at least a part of the coating, for example, the outermost layer of the coating, is in a particle shape. The latent heat storage particles obtained by the hybridization according to this embodiment can be used, for example, to form a heat exchange material.
[0051] The latent heat storage particles according to this embodiment do not necessarily need to be heat-treated (calcined) like the latent heat storage particles so far. On the other hand, if necessary, the latent heat storage particles may be heat-treated, for example, to reduce the voids contained in the porous coating portion and form a denser film as the coating portion. When the heat treatment is performed, it may be performed under the following conditions.
[0052] [Heat treatment (calcination) as required] The heat treatment conditions can be set to temperature and atmosphere depending on the components of the core raw material particles and the desired coating part. For example, the heat treatment can be performed at a temperature equal to or higher than the melting point of the latent heat storage material, for example, heating to 700°C or higher depending on the melting point of the components of the core raw material particles. In this heat treatment, the coating part formed by the hybridization is oxidized, and for example, a stronger aluminum oxide film can be formed. The aluminum oxide film formed by the heat treatment is in the γ-Al2O3 crystal form at a relatively low temperature of about 800°C or lower, and the chemically stable α-Al2O3 film is obtained at a relatively high temperature of about 880°C or higher. In order to obtain a chemically stable α-Al2O3 film, it is preferable to set the heat treatment temperature to 880°C or higher. For example, it is preferable to set it to 880°C or higher and 1230°C or lower. When the core raw material particles are, for example, an Al-Si alloy, the heat treatment can be performed at a temperature of 900°C or higher and 1230°C or lower. On the other hand, when the core raw material particles are made of, for example, Sn, the particles burn at about 600°C in an oxidizing atmosphere, so that the heat treatment can be carried out at a temperature lower than 600°C.
[0053] The atmosphere of the heat treatment is not particularly limited. For example, the atmosphere may be air, or oxygen gas may be supplied to a heat treatment furnace to create an oxygen atmosphere. The temperature in the furnace is increased by a heater, and from the point when the temperature of the sample reaches a predetermined temperature, a heat treatment (oxidation treatment) is performed for, for example, 3 to 5 hours to obtain latent heat storage particles after the heat treatment. For example, the heat treatment method may be specifically performed by filling the latent heat storage particles obtained by the hybridization described above into a crucible, placing the crucible on top of a thermocouple provided at the tip of an insertion rod, and setting the crucible in a heat treatment furnace equipped with a heater. EXAMPLES
[0054] The present invention will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples, and can be modified as appropriate within the scope of the above and below-mentioned aims, and all such modifications are included in the technical scope of the present invention.
[0055] [Example 1] In Example 1, core raw material particles whose component is Sn and whose average particle size is shown in Table 1, and child particles whose component is α-Al2O3 and whose average particle size is 0.3 μm were prepared so that the ratio (volume ratio) of child particles to the total of core raw material particles and child particles was as shown in Table 1. Then, using a high-velocity airflow impact device manufactured by Nara Machinery Works, Ltd., a process of colliding the core raw material particles with the child particles was performed by the high-velocity airflow impact method under the conditions shown in Table 1 to obtain a sample (latent heat storage particles). Note that in both Example 1-1 and Example 1-2, no heat treatment was performed after hybridization.
[0056] [Table 1]
[0057] (Repeated test (repeated durability test)) Using the sample of Example 1-1, a test was conducted in which melting and solidification were repeated 10 or 100 times. In detail, the sample was held at 400°C for 1 hour in an air atmosphere, then returned to room temperature, and then, as a first test, the temperature was raised to 400°C and held for 10 minutes, and then the temperature was lowered to 40°C and held for 10 minutes. As a second test, the temperature was raised to 400°C again and held for 10 minutes, and then the temperature was lowered to 40°C and held for 10 minutes (both the temperature rise rate and the temperature fall rate were 30°C / min). This was repeated 10 or 100 times in total. SEM observation and XRD measurement of the sample before and after the 100-time repeated test, and DSC measurement before and after the 10-time repeated test were performed as follows.
[0058] (SEM observation) The appearance and cross section of the sample of Example 1-1 before and after the 100-time melting and solidification repeated test were observed with a SEM (JEOL, JSM-7001FA). The results are shown in Fig. 2 and Fig. 3, respectively. The dark gray Al in the center photograph of Fig. 2 is the detection of Al constituting aluminum oxide. As is clear from Fig. 2, it was confirmed that the surface of the sample (latent heat storage particle) was almost covered with an aluminum oxide layer. The lower right photograph of Fig. 2 is an enlarged photograph of the area enclosed by the dashed line in the lower left photograph of Fig. 2. As shown in this lower right photograph of Fig. 2, fine particles are deposited on the outer edge (outermost layer) of the coating part, and it can be seen that at least a part of the coating part is in a particle shape. It was also confirmed that this deposit contains Al. That is, it was confirmed that an Al2O3 layer (=shell) of about 500 nm was formed on the surface of the core particle by hybridization. Also, in the lower diagram of Fig. 3, the black part in the center indicates the detection of Sn, and the gray part close to white around it indicates the detection of Al and O. As is clear from the lower image of Figure 3, Al and O were detected in the coating. This shows that even after the test was repeated 100 times during melting and solidification, a shell formed of Al2O3 was still present, preventing leakage of the PCM.
[0059] (XRD measurement) XRD measurements were performed under the following conditions using the sample of Example 1-1 before and after the 100-cycle melting and freezing test. The results are shown in Figure 4. From Figure 4, it can be seen that the crystal structure is almost unchanged before and after the 100-cycle melting and freezing test, and that the crystal structure before the test is maintained even after the 100-cycle melting and freezing test.
[0060] (Measurement conditions) X-ray diffraction equipment: Rigaku MiniFlex600 ·X-ray source: Cu ray Detector: High-speed 1D detector D / teX Ultra2 Tube voltage: 40kV ·Tube current: 15mA Scan speed: 1.0° / min Step: 0.01°
[0061] (Differential Scanning Calorimetry (DSC)) Using the sample of Example 1-1 before and after the 10-time melting and solidification repeated test, differential scanning calorimetry was performed in an alumina pan at a temperature rise rate of 10°C / min in the range of 25 to 400°C under an Ar atmosphere using a differential scanning calorimeter (METTLER TOLEDO, model number TGA / DSC3+) to obtain a DSC curve. The results are shown in FIG.
[0062] From FIG. 5, it was found that the sample of Example 1-1 retained about 80% of the latent heat of the raw material (Raw Sn Powder). In addition, the melting peak of the sample after hybridization was the same as that of the Sn powder raw material, but the solidification peak of the sample after hybridization was slightly shifted from that of the Sn powder raw material, indicating that some supercooling had occurred. As described above, the heat dissipation start temperature was lowered (supercooling), confirming that encapsulation by hybridization had been achieved. Furthermore, even after 10 repeated melting and solidification tests, the DSC curve was almost the same as that after hybridization and did not change, indicating that the capsules were not destroyed and the core-shell structure was maintained even after 10 repeated melting and solidification tests.
[0063] (Heat durability test) Using the sample of Example 1-1, a thermal durability test was carried out in an Ar atmosphere, in which the sample was heated to 300°C or 400°C, which is higher than the melting point (232°C) of Sn constituting the core particle, at a heating rate of 10°C / min, and then naturally cooled. The appearance of the sample after the thermal durability test was observed by SEM. The results are shown in FIG.
[0064] In FIG. 6, the upper row is a photograph of a sample heat-treated at 300°C, and the lower row is a photograph of a sample heat-treated at 400°C. In the upper and lower photos in the center of FIG. 6, the dark gray on the particle surface indicates the detection of Al. From the photo in FIG. 6, no melting or expansion of the shell due to heat treatment was confirmed, and there was no leakage of Sn or defects on the particle surface, and it was confirmed that the capsule structure was maintained. From this, it can be seen that the latent heat storage particles according to this embodiment have excellent thermal durability.
[0065] Using the sample of Example 1-1, the test was repeated 10 times or 100 times as described above. Then, XRD measurement was performed under the above conditions for each of the results after hybridization but before the repeated test, after 10 repeated tests, and after 100 repeated tests. The results are shown in Figure 7. In Figure 7, A shows the result after hybridization but before the repeated test, B shows the result after 10 repeated tests, and C shows the result after 100 repeated tests.
[0066] From the results of FIG. 7, it was found that the oxidation of Sn progressed as the number of repeated tests increased, and a SnO peak was observed at the 10th repeated test, and a SnO2 peak was observed at the 100th repeated test.
[0067] The sample of Example 1-1 was used and SEM observation was performed in the same manner as described above. The obtained SEM photographs are shown in FIG. 8. The left photograph in FIG. 8 is a photograph after hybridization and before the repeated test, and the right photograph in FIG. 8 is a photograph after 100 repeated tests. In each of the left and right photographs in FIG. 8, the lower photograph is a photograph in which the white square frame in the upper photograph is enlarged. From the photograph in FIG. 8, it can be seen that the shape of the Al2O3 particles constituting the coating portion remains stable with almost no change even after 100 repeated tests.
[0068] Further, the sample of Example 1-1 was used to carry out mapping analysis using a scanning transmission electron microscope (STEM) equipped with an energy dispersive X-ray analyzer (EDS). The sample obtained in the example was thinned using a focused ion beam device (JEOL, JEM-9320FIB) to obtain a sample for STEM-EDS observation. The conditions for the thinning were an acceleration voltage of 30 kV and Ga liquid metal was used as the ion source. For STEM-EDS observation, a transmission electron microscope (JEOL, product number: JEM-ARM200F) equipped with an energy dispersive X-ray analyzer (JEOL, product number: JED-2300T) was used. The observation conditions were an acceleration voltage of 200 kV and a beam diameter of 1 nm. As the observation result, a STEM-EDS photograph of the boundary region between the core particle and the coating portion is shown in FIG. 9. In FIG. 9, from the top, photographs are shown before the repeated test after hybridization, after 10 repeated tests, and after 100 repeated tests. In each photograph, from left to right, a HAADF (High-angle Annular Dark Field) image, a Sn mapping image, an Al mapping image, and an O (oxygen) mapping image are shown. These images in Figure 9 show that in the boundary region between the core particle and the coating, the components of the core particle are mixed with Al2O3 in the coating.
[0069] Furthermore, the particles constituting the coating of the latent heat storage particles were observed. As a result, Fig. 10 shows a photograph after hybridization but before the repeated test, Fig. 11 shows a photograph after 10 repeated tests, and Fig. 12 shows a photograph after 100 repeated tests.
[0070] In Fig. 10, A is a photograph of a plurality of particles constituting the coating of the latent heat storage particle, B is a cross-sectional photograph of one particle constituting the coating, C is an enlarged photograph of i in photograph B, and D is an enlarged photograph of ii in photograph B. From B to D in Fig. 10, the particles constituting the coating are formed of a light gray interior and a dark gray layer as shown in B, the dark gray layer is amorphous as shown in D, and multiple white lumps as shown in i in photograph B were observed inside the light gray, and the white lumps as shown in i were Sn as shown in photograph C. That is, it was found that the particles constituting the coating are Al2O3 particles containing metallic Sn inside.
[0071] In Fig. 11, A is a photograph of multiple particles that make up the coating of the latent heat storage particle, B is a photograph of the appearance of one of the multiple particles, and C is an enlarged photograph of iii in B. These photographs show that after 10 repeated tests, a large amount of SnO, shown in gray close to white in B, is present on the surface of the particles that make up the coating.
[0072] Furthermore, in Figure 12, A is a photograph of multiple particles that make up the coating of the latent heat storage particle, B is a cross-sectional photograph of a single particle that makes up the coating, and C to E are enlarged photographs of iv to vi in photograph B. From these photographs, it can be seen that after 100 repeated tests, in the cross-sectional photograph of a single particle that makes up the coating in B, the inside of the particle contains SnO2 (iv), shown in a gray color close to white, in α-Al2O3 (v), shown in a light gray color. It can also be seen that a crystal structure of Sn oxide and Al oxide is present in vi, which is near the surface of the particle that makes up the coating.
[0073] The sample of Example 1-1 was also used to investigate the effect of the number of repeated tests on the results of differential scanning calorimetry. As a result, the results of differential scanning calorimetry after 1, 10, 25, 50, and 100 repeated tests are shown in Figure 13. Figure 14 shows the change in latent heat at melting and solidification versus the number of repeated tests, as well as the shift in the peak solidification temperature.
[0074] The observation results and measurement results in the above-mentioned Figs. 7 to 14 reveal the following. First, it can be seen that the surface of the latent heat storage particle is not densely covered with α-Al2O3 constituting the coating portion, but the Sn exposed parts of the core particle are scattered, and Sn, a component of the core particle, is embedded in α-Al2O3 constituting the coating portion. This is presumed to be due to the fact that when the latent heat storage particle according to this embodiment is produced by hybridization, the α-Al2O3 particles, which are child particles, collide with the Sn particles, which are the core raw material particles, and Sn is repeatedly attached to the α-Al2O3 particles. It is also considered that the Sn in the α-Al2O3 is oxidized by the repeated test, and SnO is formed. Furthermore, it is considered that the oxidation progresses as the number of repeated tests increases, and SnO2 is present. It is considered that the above phenomenon is also observed in latent heat storage particles obtained by performing heat treatment after hybridization instead of the repeated test.
[0075] In addition, in Figure 14, the amount of latent heat remains almost constant after 60 repeated tests. This is thought to be because, for example, in areas where the core particle has scattered Sn exposed parts, the Sn that constitutes the core particle is consumed as oxide as the number of repeated tests increases, but as the number of repeated tests increases, the amount of Sn oxide increases in the boundary region between the core particle and the coating, which acts as an oxidation prevention layer to stop the oxidation of Sn, and as a result, the amount of latent heat stabilizes.
[0076] [Example 2] In Example 2, core raw material particles containing Sn with an average particle size of 150 μm and child particles containing Al with an average particle size of 2 μm were prepared in a compounding ratio in which the ratio of the child particles to the total raw material particles was 40 vol% (volume %). A photograph of the appearance of these raw material particles is shown in FIG. 15. These raw material particles were put into a high-speed airflow impact device as in Example 1, and hybridization was performed by colliding the Al child particles with the Sn core raw material particles by the high-speed airflow impact method under the conditions of a peripheral speed of 80 m / s and a processing time of 3 minutes, to obtain a sample. In Example 2, no heat treatment was performed after hybridization.
[0077] (SEM observation after hybridization) The cross section of the sample (latent heat storage particles) after hybridization was observed with an SEM (JEOL, JSM-7001FA), and EDS analysis (energy dispersive X-ray spectroscopy) was also performed. The results are shown in Figure 16. In the EDS analysis results on the right side of Figure 16, the gray area close to the black in the center of each particle indicates the detection of Sn, and the shell-like light gray area surrounding it indicates the detection of Al. From Figure 16, it was found that encapsulation is possible even when Al is used as the child particle, just like when Al2O3 is used as the child particle in Example 1, and latent heat storage particles of the micron order can be produced.
[0078] (Repeated test (repeated durability test)) Using the sample of Example 2, a melting and solidification cycle test was carried out in the same manner as in Example 1, except that the number of cycles was 50. Then, EDS analysis was carried out on the appearance and cross section of the sample (latent heat storage particles) before and after the 50-cycle melting and solidification test. The results are shown in FIG.
[0079] In the EDS analysis results shown on the right in Figure 17, the gray area close to black in the center of each particle indicates the detection of Sn, and the light gray shell-like area surrounding it indicates the detection of Al. From Figure 17, a photograph of the sample (latent heat storage particle) before the 50-time melting and solidifying repeated test, and the photograph in Figure 16, it can be seen that Al fine particles are fixed to the surface of the obtained sample (latent heat storage particle) to form a "layered" shell. Furthermore, Al is detected in the shell part and Sn is detected in the core part, and it can be seen that a Sn-Al core-shell structure is formed. It can also be seen that this structure is maintained even after the 50-time melting and solidifying repeated test. The reason why a "layered" shell was able to be formed on the surface of the core particle in this way is thought to be that after the Al child particles are fixed to the surface of the core particle, the Al child particles fixed to the surface are crushed by the impact of the other Al child particles colliding one after another, forming a layered shell. In addition, in Example 2, core particles of a somewhat large size were used. However, even in this case, it was found that a shell could be formed uniformly on the surface of the core particles by adjusting the processing conditions, such as the ratio of child particles to core particles.
[0080] [Example 3] In Example 3, Al-25 mass% Si having an average particle size of 20-37 μm was used as the core particles, and various Al compounds shown in Table 2 were used as the child particles. Hybridization was performed in the same manner as in Example 1 under the conditions shown in Table 2 below to obtain samples. After hybridization, heat treatment was performed under the conditions shown in Table 2.
[0081] [Table 2]
[0082] (SEM observation before and after heat treatment) The appearance of the latent heat storage particles before and after the heat treatment was observed with a SEM (JEOL, JSM-7001FA), and EDS analysis was also performed. As a result, a SEM micrograph of the sample before the heat treatment (child particles are α-Al2O3, AlOOH) is shown in FIG. 18, a SEM micrograph of the appearance of the sample after the heat treatment (child particles are α-Al2O3) and the EDS analysis results are shown in FIG. 19, a SEM micrograph of the appearance of the sample after the heat treatment (child particles are α-AlOOH) and the EDS analysis results are shown in FIG. 20, and a SEM micrograph of the appearance of the sample after the heat treatment (child particles are Al(OH)3) and the EDS analysis results are shown in FIG. 21. In addition, a SEM micrograph of the cross section of each sample after the heat treatment at 1000°C and the EDS analysis results are shown in FIG. 22. In each of the photographs in FIG. 19 to FIG. 21, the photograph on the lower left of the four photographs shown by temperature shows the EDS analysis results, where dark gray indicates the detection of Al, and gray that is not covered by dark gray and is close to white indicates the detection of Sn. In addition, in the EDS analysis results in the middle rows of each section of Figure 22, the gray close to black on the particle cross section indicates detection of Si, the light gray around it indicates detection of Al, and the gray parts on the particle surface indicate detection of Al and O. These photographs show that a coating containing Al is formed uniformly on the surface of the core particle both before and after heat treatment, with almost no gaps. Also, from the photographs in the bottom rows of Figure 22, it can be seen that an aggregate of particles derived from child particles is formed on the surface of the coating, and at least a part of the coating is in a particle shape.
[0083] (XRD measurement after heat treatment) XRD measurement of the latent heat storage particles after heat treatment was carried out in the same manner as in Example 1. The results are shown in Figure 23 for the sample heat-treated at 1000°C and in Figure 24 for the sample heat-treated at 1150°C. From these figures, it was found that in all samples after heat treatment at high temperatures, the core was formed of Al-Si and α-Al2O3 was formed in the coating.
[0084] (DSC measurement after heat treatment) DSC measurement of the latent heat storage particles after heat treatment was carried out in the same manner as in Example 1. The results are shown in FIG. 25 for the samples heat treated at 1000°C. From this figure, it can be seen that all samples after heat treatment at high temperatures maintained a high latent heat of 200 J / g or more, and are useful as high-density heat storage materials. Moreover, the results of the samples heat treated at 1150°C are shown in FIG. 26. From this figure, it can be seen that all samples showed a high latent heat of 150 J / g or more, even after heat treatment at higher temperatures.
[0085] (SEM observation after repeated testing) A repeat test was carried out 100 times in the same manner as in Example 1, except that the latent heat storage particles of Example 3-1 using α-Al2O3 as the child particles were used and the atmosphere was an oxygen atmosphere with an oxygen concentration of 21%. The appearance of the latent heat storage particles before and after the repeat test was observed with a SEM (JEOL, JSM-7001FA), and EDS analysis was also carried out. As a result, photographs before and after the repeat test are shown in FIG. 27. In the EDS analysis results shown in the lower part of FIG. 27, the dark gray on the surface of each particle indicates the detection of Al, and the near-white gray observed in some particles indicates the detection of Sn. From FIG. 27, it was confirmed that there was almost no change in both appearance and composition even after the repeat test, there was no leakage of PCM, the shape was maintained, and high durability was demonstrated.
[0086] [Example 4] In Example 4, Zn-10 mass%Al having a particle size of 10 μm or more and less than 38 μm undersize was used as the core particles, and AlOOH was used as the child particles in various volume ratios shown in Table 3. The total amount of the core particles and the child particles was 30 g. Hybridization was performed in the same manner as in Example 1 under the conditions shown in Table 3 below. The peripheral speed of 80 m / s in Table 3 corresponds to 13,000 rpm. The atmosphere in the collision chamber of the high-speed airflow impact device used for hybridization was an Ar atmosphere. After hybridization, heat treatment was performed under the conditions shown in Table 3 to obtain samples. The heating and cooling rates from room temperature to the heat treatment temperature shown in Table 3 were 50° C. / min.
[0087] [Table 3]
[0088] (Repeated test (repeated durability test)) Using the samples of Examples 4-1 and 4-3, a test was conducted in which melting and solidification were repeated 300 times. In detail, the temperature was raised from room temperature to 250°C at 50°C / min in an air atmosphere, and then held at 250°C for 10 minutes. After that, the temperature was raised from 250 to 500°C as a first run, held at 500°C for 2 minutes, and then lowered to 250°C and held for 2 minutes. Then, the temperature was raised again from 250 to 500°C as a second run, held at 500°C for 2 minutes, and then lowered to 250°C and held for 2 minutes (both the temperature rise rate and temperature fall rate were 50°C / min), and this was repeated a total of 300 times.
[0089] (SEM observation before and after heat treatment and after repeated testing) The appearance of the latent heat storage particles before and after the heat treatment and after the cyclic test was observed with a scanning electron microscope (SEM, manufactured by JEOL Ltd., product number: JSM-7001FA). As a result, the SEM micrograph of the sample with a volume ratio of the child particles of 20 vol% is shown in FIG. 28, the SEM micrograph of the sample with a volume ratio of the child particles of 30 vol% is shown in FIG. 29, and the SEM micrograph of the sample with a volume ratio of the child particles of 40 vol% is shown in FIG. 30. In this embodiment, "After Hybridixed" in the drawings indicates the results of the sample after hybridization and before the heat treatment, "After heat-oxidation treatment" indicates the results of the sample after the heat treatment and not subjected to the cyclic test, and "After cyclic test of 300 times" indicates the results of the sample after the cyclic test. The same applies below.
[0090] (DSC measurements before and after repeated testing) DSC measurements of the samples before and after the repeated test were performed in the same manner as in Example 1. As a result, the DSC measurement result (after heat treatment) of the sample with a volume ratio of child particles of 20 vol% is shown in Fig. 31, the DSC measurement result (after heat treatment) of the sample with a volume ratio of child particles of 20 vol% (after 300 repeated tests) is shown in Fig. 32, the DSC measurement result (after heat treatment) of the sample with a volume ratio of child particles of 30 vol% is shown in Fig. 33, the DSC measurement result (after heat treatment) of the sample with a volume ratio of child particles of 40 vol% is shown in Fig. 34, and the DSC measurement result (after 300 repeated tests) of the sample with a volume ratio of child particles of 40 vol% is shown in Fig. 35.
[0091] These figures show that all samples encapsulated with Zn alloys having a melting point of approximately 380°C exhibit the same properties even after the cyclic tests as they did before the cyclic tests.
[0092] [Example 5] In Example 5, as shown in Table 4, Al-26.5 mass% Cu-5.4 mass% Si with an average particle size of 25 to 38 μm was used as the core particle, and α-Al2O3 was used as the child particle. The total amount of the core particle (15.37 g) and the child particle (4.63 g) was 20 g. Hybridization was performed in the same manner as in Example 1 under the conditions in Table 4 below. The atmosphere in the collision chamber of the high-speed airflow impact device used for hybridization was an Ar atmosphere. After hybridization, heat treatment was performed under the conditions shown in Table 4 to obtain a sample. The temperature was increased from room temperature to the heat treatment temperature shown in Table 4 at 10° C. / min.
[0093] [Table 4]
[0094] (Repeated test (repeated durability test)) Using the sample of Example 5-1, a test was conducted in which melting and solidification were repeated 100 times. In detail, after the sample was prepared, it was cooled from 1000°C to 300°C at 50°C / min in an air atmosphere, held at 300 for 10 minutes, and then returned to room temperature. After that, the temperature was raised from 300°C to 650°C as the first time, held at 650°C for 2 minutes, and then lowered to 300°C and held for 2 minutes. Then, the temperature was raised from 300°C to 650°C again as the second time, held at 650°C for 2 minutes, and then lowered to 300°C and held for 2 minutes (both the heating rate and the cooling rate were 50°C / min), and this was repeated a total of 100 times.
[0095] (SEM observation before and after heat treatment and after repeated testing) The appearance of the latent heat storage particles before and after the heat treatment and after the repeated test was observed using a SEM (JEOL, JSM-7001FA). The results are shown in Figure 36.
[0096] (DSC measurements before and after repeated testing) DSC measurements of the samples before and after the repeated test were performed in the same manner as in Example 1. The results are shown in FIG. 37. FIG. 37 shows the results of the sample after the heat treatment but not the repeated test, and the sample after 100 repeated tests. In FIG. 37, the heat of fusion ΔH of the latent heat storage particles after the heat treatment was 291 J / g, and the heat of fusion ΔH of the latent heat storage particles after the repeated test was 300 J / g. In addition, the heat of solidification ΔH of the latent heat storage particles after the heat treatment was 286 J / g, and the heat of solidification ΔH of the latent heat storage particles after the repeated test was 281 J / g.
[0097] From these figures, it can be seen that the sample encapsulated with an Al alloy having a melting point of approximately 525°C exhibits the same surface condition and properties even after the cyclic test as before the cyclic test.
[0098] [Example 6] In Example 6, as shown in Table 5, Sn-9 mass% Zn with a sieve size of less than 45 μm was used as the core particle, and α-Al2O3 was used as the child particle. The total amount of the core particle (26.46 g) and the child particle (3.54 g) was 30 g. Hybridization was performed in the same manner as in Example 1 under the conditions in Table 5 below to obtain a sample. The atmosphere in the collision chamber of the high-speed airflow impact device used for hybridization was an Ar atmosphere. In Example 6, no heat treatment was performed after hybridization.
[0099] [Table 5]
[0100] (SEM observation of raw material (core particle) and after hybridization) The appearance of the raw material (core particle) and the sample after hybridization were observed with an SEM (JEOL, JSM-7001FA). The results are shown in Figure 38. In Figure 38, the "Raw material" in the upper row is an SEM observation photograph of the raw material (core particle).
[0101] (DSC measurements of raw material (core particles) and after hybridization) DSC measurements of the raw material (core particles) and the sample after hybridization were carried out in the same manner as in Example 1. As a result, Fig. 39 shows the DSC measurement results of the raw material, and Fig. 40 shows the DSC measurement results of the sample after hybridization.
[0102] From these figures, it can be seen that the sample after hybridization has the same properties as the raw material (core particles).
[0103] As shown in the above examples, the present disclosure has achieved microencapsulation of metal PCMs that do not contain Al or are mainly composed of elements other than Al. Furthermore, it has achieved latent heat storage particles of micron order whose coating portion is formed of metal or ceramics other than Al2O3, which has not been realized until now. Furthermore, it has become possible to more easily microencapsulate Al alloy PCMs.
[0104] This application claims priority from Japanese Patent Application No. 2021-145531, which is incorporated herein by reference. [Explanation of symbols]
[0105] 1 Raw material particle inlet 2 Rotors 3 Blades 4 Stator 5 Circulation circuit 6. Exhaust valve 7 Outlet 8. Core raw material particles 9. Child Particles 10 Latent heat storage particles 100 High-velocity airflow impact device
Claims
1. The present invention has a core particle and a coating portion that coats at least a portion of the surface of the core particle, The component of the core particle is an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy containing these as main components, and has a melting point of 100° C. or higher; a component of the coating portion is one or more selected from the group consisting of an element, an alloy and an inorganic compound containing the element, and a mixture thereof, which does not undergo a chemical reaction with the core particle in a temperature range of an operating temperature and is different from the component of the core particle; At least a part of the coating portion is in a particle shape.
2. The latent heat storage particles according to claim 1 , wherein the average particle diameter of the core particles is 10 μm or more and 200 μm or less.
3. The latent heat storage particle according to claim 1 or 2, wherein at least a part of the particle shape of the coating portion has an average particle diameter of 0.1 μm or more and 2 μm or less.
4. 3. The latent heat storage particle according to claim 1, wherein the component of the core particle is one or more selected from the group consisting of Al, an Al-Si alloy, an Al-Cu-Si alloy, Sn, an Sn alloy, and a Zn-Al alloy.
5. The inorganic compounds in the components of the coating portion include ceramics, glass, and α-Al 2 O 3 The latent heat storage particle according to claim 1 or 2, which is at least one selected from the group consisting of α-alumina precursors represented by the formula (1) and (2).
6. The components of the coating portion are Al, α-Al 2 O 3 , AlOOH, Al(OH) 3 3. The latent heat storage particle according to claim 1, which is one or more selected from the group consisting of: and glass.
7. The latent heat storage particle according to claim 1 or 2, wherein the coating portion contains one or more selected from the group consisting of an element constituting the core particle, an alloy and an inorganic compound containing the element, and a mixture thereof.
8. A heat exchange material formed from the latent heat storage particles according to claim 1 or 2.
9. A core raw material particle having a melting point of 100° C. or higher, the component of which is an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy containing these as main components; A child particle is prepared, the child particle having a component selected from the group consisting of an element, an alloy and an inorganic compound containing the element, and a mixture thereof, the component being different from the component of the core material particle and not chemically reacting with the core material particle in a temperature range of an operating temperature; and The core material particles and the child particles are collided with each other by an impact method in a high-speed air stream, thereby performing hybridization in which the child particles are fixed to the surfaces of the core material particles. A method for producing latent heat storage particles, comprising:
10. The average particle size of the core raw material particles is 10 μm or more and 200 μm or less, The average particle size of the child particles is 0.1 μm or more and 2 μm or less, The method for producing latent heat storage particles according to claim 9 , wherein a ratio of (average particle size of child particles / average particle size of core raw material particles) is 0.001 or more and 0.2 or less.
11. The method for producing latent heat storage particles according to claim 9 or 10, wherein the hybridization is carried out at a peripheral speed of 40 m / s or more and 100 m / s or less.
12. The method for producing latent heat storage particles according to claim 9 or 10, further comprising carrying out a heat treatment at a temperature equal to or higher than the melting point of the component of the core raw material particle after the hybridization.
Citation Information
Patent Citations
Latent heat storage capsule
JP1999023172A
Heat storing body and method
JP2012111825A
Heat storage microcapsule and method for manufacturing the same
JP2012140600A
Latent heat storage body micro-capsule, method for manufacturing latent heat storage body, heat exchanging material, and catalytic functional latent heat storage body
JP2019173017A
Latent heat storage body, method for producing latent heat storage body, and heat exchange material
JP2019203128A